ANALISIS KEBIJAKAN SERTIFIKASI PRODUK HALAL DALAM PERSPEKTIF PERLINDUNGAN KEMASLAHATAN UMAT - Khabib Solihin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2020)
Abstract The policy on Halal Product Certification in Indonesia has been formally regulated in the Constitution Republic of Indonesia No. 33 of 2014 concerning Guaranteed Halal Products and Government Regulation of the Republic of Indonesia No. 31 of 2019 concerning the Implementation of Law No. 33 of 2014 concerning Halal Product Guarantee. The issuance of the policy received various responses and caused various polemics in the community, among the responses and polemics that arose in the community was the rejection of the implementation of the policy caused by the lack of readiness of micro and medium enterprises in carrying out the policy, disrupted economic stability due to the number of UMKM that have not been carry out these obligations, as well as other polemics that lead to the unpreparedness of this regulation to be enforced compulsorily to all business actors and the products they produce, most of the responses and polemics arising from several business community communities lead to negative assessments of regulations determined by the government. Apart from these polemics, this research was conducted to see the positive side of the halal certification policy in the perspective of protecting the benefit of the people, this research is a descriptive qualitative research that results in a conclusion that the policy of halal product certification has a positive side relating to the protection of the benefit of the people and deserves for all parties to strive for its implementation Keywords : Halal Product Certification, Maslahah Umat